The Wisdom of the Aramaic Book of Ahiqar : Unravelling a Discourse of Uncertainty and Distress - Bledsoe, Seth (Supplements to the Journal for the Study of Judaism, 2022)
This book offers fresh readings of the Aramaic book of Ahiqar, an oft underappreciated ancient wisdom text. In undertaking a comprehensive literary analysis, incorporating both the drama and the sayings together, Bledsoe shows that Ahiqar's didactic impulse is founded on a sense of uncertainty about life, offering advice for those in times of distress, much like the titular character himself. While Ahiqar shares many features with instructional literature like Proverbs, the ambiguous cosmic and social order imagined in the text resonate more strongly with the likes of Qoheleth or Job. Bledsoe also takes seriously the Elephantine context, suggesting that the social and political ethic evinced by the work would have resonated strongly with the Judean community in Achaemenid Egypt.